RESERVING BROTHERHOOD AND KINDNESS: MEGENGAN TRADITION IN WELCOMING RAMADHAN MONTH - Rochmat Budi Santosa; Bayu Wiratama (International Conference on Social and Islamic Studies, 2021)
This study discussed about Megengan tradition. Megengan tradition is a religious tradition inJavanese culture. This tradition started to grow up in society in a long history. The aims of this researchis to explore and find meaningful messages in this unique tradition. Besides for welcoming Ramadhan,this tradition also for praying for our family member who had died. This tradition makes a uniquecharacteristic in society, how culture and Islam are still conserved in one field although both of them arein different fields. It means that society do not avoid the tradition from their ancestry. The researchersused descriptive qualitative with ethnography design. This research’s aim is to describe more detailabout Megengan tradition in Ngancar, Wonogiri. The result of this research show that Megengantradition still exist in society to conserve the old tradition.